ANALISA PENYUSUTAN KENDARAAN TERHADAP LAPORAN KEUANGAN PADA DINAS PENGELOLA PENDAPATAN KEUANGAN DAN ASET DAERAH KOTA CIREBON - Agus Yudianto; Autami Tri Lestari (BBM (Buletin Bisnis & Manajemen), 2020)
Affairs of local government based on the principles of autonomy and duty auxiliary fields opinion, financial and asset management area. The main function of accounting in the calculation not to benefit as much as it is a function of efficiency in managing funds that are set to not having swelling funds.In this office for the cost of vehicles by the end of 2011 was Rp. 980,658,541.00. Assets of these vehicles in the estimate has economic life for five years, whereas the residual value at the end of 2015 there was Rp. 885,658,541.00. In the calculation using the straight-line method of depreciation expense each year will be a constant that will ease the calculation.